Comparisons of +3179G/A insulin-like growth factor 1 receptor gene distribution between two inflammatory arthritides and healthy adults - Mariana IVANOVA; Irena MANOLOVA; Rumen STOILOV; Spaska STANILOVA (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate whether single nucleotide polymorphisms (SNPs) at the +3179G/A insulin-like growth factor 1 receptor (IGF-1R) locus were associated with rheumatoid arthritis (RA) and ankylosing spondylitis (AS) genetic susceptibility and also explore age and sex distribution of the rs2229765 in healthy adults. Patients and methods: This cross-sectional study was conducted between September 2012 and October 2014. Seventy patients with RA (7 males, 63 females; mean age: 54±1 years; range, 32 to 78 years) and 56 with AS (44 males, 12 females; mean age: 38±9 years; range, 22 to 57 years) were genotyped using polymerase chain reaction-restriction fragment length polymorphism method. The genotype and allele frequencies of the rs2229765 polymorphism in both patient groups were compared to those in 308 healthy donors (141 males, 167 females; mean age: 35±19 years; range, 18 to 75 years) who were further subjected to analysis of sex- and age-related genetic variation. Results: We identified the homozygous genotype AA (22.9% vs. 14.1%; odds ratio [OR]=2.33, p=0.034) and A-allele (47.9% vs. 37.5%; OR=1.53, p=0.032) associated with increased risk for RA, but not AS. The same genotype AA was non-significantly more common in healthy males than females, and the frequency of the A-allele was markedly higher in younger males (46% vs. 40%; p=0.039). The overall percentage of healthy carriers of the AA gene variant was 18%. Conclusion: We primarily present an inverse effect of the +3179G/A IGF-1R polymorphism on disease susceptibility to RA and AS, confirming the distinctly different immune pathways involved in the pathogenesis of both inflammatory arthritides. In addition, we could also show trends regarding age- and sex-specific patterns of the rs2229765 genotype distribution in the general population.